Remunerasi Salah Satu Faktor Penekan Angka Korupsi - Muhammad Dani Ramadansyah (Center fo State Civil Apparatus Training and Development and Competency Mapping, 2009)
Corruption is the biggest crime in a country. There are so many official government has been included in corruption that makes them got in jail. Government has an idea in decreasing corruption phenomena that is remuneratism. As a result, by doing so civil servant’s prosperity will be better and also will decrease a number of corruption.